2016
DOI: 10.1097/aog.0000000000001132
|View full text |Cite|
|
Sign up to set email alerts
|

Gestational Diabetes Screening

Abstract: Although one-step screening was associated with more patients being treated for gestational diabetes, it was not associated with a decrease in large-for-gestational-age or macrosomic neonates but was associated with an increased rate of primary cesarean delivery. Our results did not support the IADPSG-recommended screening protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 16 publications
2
33
1
Order By: Relevance
“…A retrospective analysis by Ethridge et al (5) also suggested women who would be diagnosed with GDM based on IADPSG criteria have significant increases in adverse pregnancy outcomes compared with women undergoing normal GDM screening. These findings contrast with other data, including a recent publication by Feldman et al (7), which cited an increased number of women diagnosed with GDM when using IADPSG criteria, but no difference among large-for-gestational-age newborns or those with macrosomia when either the CC or IADPSG criteria were used. Because of the lack of clarity regarding the additional benefit of universal one-step testing with IADPSG criteria, ACOG continues to recommend traditional testing with a 50-g screen and a diagnostic 100-g OGTT (2).…”
Section: Discussioncontrasting
confidence: 99%
“…A retrospective analysis by Ethridge et al (5) also suggested women who would be diagnosed with GDM based on IADPSG criteria have significant increases in adverse pregnancy outcomes compared with women undergoing normal GDM screening. These findings contrast with other data, including a recent publication by Feldman et al (7), which cited an increased number of women diagnosed with GDM when using IADPSG criteria, but no difference among large-for-gestational-age newborns or those with macrosomia when either the CC or IADPSG criteria were used. Because of the lack of clarity regarding the additional benefit of universal one-step testing with IADPSG criteria, ACOG continues to recommend traditional testing with a 50-g screen and a diagnostic 100-g OGTT (2).…”
Section: Discussioncontrasting
confidence: 99%
“…In our search of the literature we found only two retrospective cohorts that compared the treatment effect on maternal and neonatal outcomes between groups who received Carpenter-Coustan versus IADPSG testing. 67 Huang and Hsieh 6 found that, compared to women who underwent Carpenter-Coustan testing, those who underwent IADPSG testing had lower rates of LGA (6.3% vs. 7.8%, adjusted OR 0.74, 95% CI 0.61–0.89), but had no change in the rate of cesarean delivery, NICU admission, or preeclampsia as it was underpowered to identify differences in many of these outcomes. A second before-and-after cohort study by Feldman et al 7 found no differences in rates of LGA neonates in a Carpenter-Coustan versus a IADPSG epoch.…”
Section: Discussionmentioning
confidence: 99%
“…Two large-cohort studies were published since the consensus conference that demonstrated contradictory results both for their primary outcome of large-for-gestational-age neonates as well as for select secondary outcomes, including the total rate of cesarean delivery, primary cesarean delivery, macrosomia and neonatal intensive care unit admission. 67 …”
mentioning
confidence: 99%
“…(4) Prospective non-RCTs or retrospective studies comparing incidence of GDM and/or outcomes between the One-Step and Two-Step methods: we found 9 retrospective studies comparing the One-Step approach with IADPSG criteria and Two-Step approach with ACOG criteria (Table 4) [2230]. Regarding GDM rate, the incidence is higher for women undergoing the One-Step test in all the studies analyzing this issue.…”
Section: Screening Controversiesmentioning
confidence: 99%